2018
DOI: 10.3390/met8070488
|View full text |Cite
|
Sign up to set email alerts
|

On Oxidation Resistance Mechanisms at 1273 K of Tungsten-Based Alloys Containing Chromium and Yttria

Abstract: Tungsten (W) is currently deemed the main candidate for the plasma-facing armor material of the first wall of future fusion reactors, such as DEMO. Advantages of W include a high melting point, high thermal conductivity, low tritium retention, and low erosion yield. However, was an accident to occur, air ingress into the vacuum vessel could occur and the temperature of the first wall could reach 1200 K to 1450 K due to nuclear decay heat. In the absence of cooling, the temperature remains in that range for sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…In Figure 8, one of the main achievements is shown, the production of, and oxidation study on field-assisted sintering (FAST) produced, bulk W-Cr-Y samples. [85] In ref. [85], it is stated that to achieve full passive safety it is required that the alloy maintains the protective oxide layer for several weeks to suppress sublimation.…”
Section: W Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 8, one of the main achievements is shown, the production of, and oxidation study on field-assisted sintering (FAST) produced, bulk W-Cr-Y samples. [85] In ref. [85], it is stated that to achieve full passive safety it is required that the alloy maintains the protective oxide layer for several weeks to suppress sublimation.…”
Section: W Alloysmentioning
confidence: 99%
“…[85] In ref. [85], it is stated that to achieve full passive safety it is required that the alloy maintains the protective oxide layer for several weeks to suppress sublimation. Thus, studies for passivation of up to 467 h were performed, as shown in Figure 8.…”
Section: W Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an article on oxidation resistance of some critical components of the fusion reactors which is a cutting-edge futuristic topic [1]. Tungsten-base alloys are among main candidates for such applications because of their very high melting point, high thermal conductivity, low tritium retention, and low erosion yield.…”
Section: Contributionsmentioning
confidence: 99%
“…An issue not tackled in this contribution is the formation of radioactive and highly volatile W-oxide (WO 3 ) compounds during accidental air ingress. To suppress the release of Woxides W-based self-passivating alloys can be incorporated into the composite approach [18,19,20,21,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%